Racial capitalism and the US formula shortage: A policy analysis of the formula industry as a neocolonial system - Tomori, Cecília; Palmquist, Aunchalee E. L. (Frontiers in Sociology, 2022)
The U.S. is currently experiencing a formula shortage and an infant feeding crisis that began with a formula recall and the hospitalization of 4 infants, 2 of whom died. Since 1981, governments around the world have been calling for an end to blatant human rights violations made by the commercial milk formula (CMF) industry. These practices not only involve targeting nutritionally vulnerable populations of mothers and newborns to turn a profit, but also actively undermining the implementation of policies, legislation, and regulatory oversight that might compromise their accumulation of wealth. In this paper we analyze the 2022 formula-shortage-as-infant-feeding-crisis through the lens of the history of colonialism and critical theory in the anthropology of reproduction. First, we provide an overview of the colonial roots of the formula industry in a global perspective. We then focus on how the mechanisms of racial exploitation remain entrenched in the U.S. approach to infant feeding policies, regulation and investment, setting the stage for the current infant feeding crisis. Through our analysis of the 2022 infant feeding crisis we demonstrate how the multinational CMF industry perpetuates racial capitalism and racialized health inequities and disparities through its operations as a neo-colonial enterprise. Finally, we offer policy interventions and potential solutions that are grounded in structural interventions for more equitable, anticolonial, antiracist infant feeding systems.